Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises - Page 112: 72



Work Step by Step

$(3-i)(3+i)(2-6i)$ Begin by evaluating the product between the first two factors. The product of the first two factors represents the factored form of a difference of two squares. $(3-i)(3+i)(2-6i)=(9-i^{2})(2-6i)=...$ Substitute $i^{2}$ by $-1$ and simplify the first factor: $...=[9-(-1)](2-6i)=(9+1)(2-6i)=10(2-6i)$ Evaluate the remaining product: $...=20-60i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.